Analisis Struktur Musikal Ensambel Musik Tiup yang Disajikan pada Upacara Saur Matua dalam Konteks Kebudayaan Batak Toba di Kota Medan - Nielson Dimpu R. Sihombing (CV. Creative Tugu Pena, 2024)
The purpose of this study was to examine the musical structure of inflatable music presented at the saur matua ceremony in the Toba Batak community in Medan City. This paper will analyze the elements of the structure of wind music both melody, harmony and rhythm in the context of the ceremony of mate saur matua by using the theory function and structure and also put forward by Alan P. Merriam. The method used is several ways, namely by way of fieldwork consisting of interviews and observations, laboratory work, and literature studies. The musical structure of the inflatable music from the three songs taken has a musical structure: the scales used are pentatonic using five tones, the tone area on average consists of four and five tunings, the basic tone used is the tone F, the number of tones is the most third, the most intervals are 1P and 2M, the melody formula of the three songs is five, six and two forms. The pattern of kadens at the end is to use rising tones while the contours are static, pendulous and descending. All songs use meter four which is filled with rhythm duplex and quadruple. Harmony uses chords I, IV and V with the kadens I and V chord patterns.